BROCA’S APHASIA WORD PRODUCTION OF SODDERLAND IN "MY BEAUTIFUL BROKEN BRAIN" MOVIE - Warda Humairoh Syarifah (PARADIGM: Journal of Language and Literary Studies, 2020)
As a disorder that can hamper people's ability to use a language, aphasia is relatedto the damage that happened in the human brain. Some diseases that cause it arestroke, trauma, and brain hemorrhage. Complaints of aphasia sufferers can differfrom each other, and it is caused by the location of the disruption of languagefunction in the brain. Therefore, this study aims to analyze and observe difficultiesexperienced by Sodderland as the main character in My Beautiful Broken Brainmovie. Based on the analysis of mistakes made by Sodderland, the finding revealedthat she had difficulties in producing words, and it disturbs her interaction with thepeople around her. The errors produced are; lexical selection error, malapropism,substitution, shift, and omission. It also indicates some difficulties experienced byher; effortful speech, distortion of articulation, and stutter. Thus, the location ofbrain damage experienced by Sodderland was in the area of Broca so that sheexperienced a disruption that was dominant in language production. The articleends with some suggestions to help the people understand the difficulties peoplehave with this kind of disorder.